Plasticity of Cyanobacterial Thylakoid Microdomains Under Variable Light Conditions - Canonico, Myriam; Konert, Grzegorz; Kaňa, Radek (Frontiers in Plant Science, 2020)
Photosynthetic light reactions proceed in thylakoid membranes due to the activity of pigment-protein complexes. These complexes are heterogeneously organized into granal/stromal thylakoids (in plants) or into recently identified cyanobacterial microdomains (MDs). MDs are characterized by specific ratios of Photosystem I (PSI), Photosystem II (PSII), and Phycobilisomes (PBS) and they are visible as sub-micrometer sized areas with different fluorescence ratios. In this report, the process of long-term plasticity in cyanobacterial thylakoid MDs has been explored under variable growth light conditions using Synechocystis sp. PCC6803 expressing YFP tagged PSI. Thylakoid membrane organization into MDs has been observed for all categorized shapes of cells independently of their stage in cell cycle. The heterogeneous PSI, PSII and PBS thylakoid areas were also identified under two types of growth conditions: at continuous light and at light-dark cycle. The adaptation from continuous light to light-dark cycle was typical by changes in spatial distribution of photosystems, in particular PSI became more evenly distributed in thylakoids under light-dark cycle. The process of the spatial PSI (and partial PSII) redistribution required one week and was accompanied by temporal appearance of PBS decoupling probably caused by the re-organization of photosystems. The overall acclimation we observed was defined as thylakoid membrane plasticity as it resembles higher plants grana/stroma reorganization at variable growth light conditions. In addition, we observed large cell to cell variability in the actual MDs organization. It leads us to suggest that the plasticity, and cell to cell variability in MDs could be a manifestation of phenotypic heterogeneity, a recently broadly discussed phenomenon for prokaryotes.